Evaluation of l-tyrosine mixed with sodium dodecyl sulphate or cetyl pyridinium chloride as a corrosion inhibitor for mild steel in 1 M HCl: experimental and theoretical studies. Issue 66 (27th June 2016) - Parveen, Mosarrat; Mobin, Mohammad; Zehra, Saman
Abstract : The inhibition effect ofl -tyrosine mixed with sodium dodecyl sulphate or cetyl pyridinium chloride on mild steel corrosion in HCl was studied. Abstract : The inhibition effect ofl -tyrosine (Tyr) and Tyr mixed with sodium dodecyl sulphate (Tyr + SDS) or cetyl pyridinium chloride (Tyr + CPC) on mild steel (MS) corrosion in 1 M HCl at temperatures of 30, 40, 50 and 60 °C was studied employing gravimetric analysis, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization measurements, scanning electron microscopy (SEM), Fourier transform infra red (FTIR), UV-visible spectroscopy and theoretical calculations. The concentration of Tyr was varied between 10 and 200 ppm, whereas that of CPC or SDS was fixed at 5 ppm. Tyr inhibits the corrosion rates of MS to a considerable extent. The inhibition efficiency of Tyr is synergistically enhanced on adding SDS or CPC at all concentrations. The change in the impedance parameters indicated that Tyr and Tyr + SDS/CPC acted by adsorption at the MS/solution interface. Distinctively different surface morphologies for uninhibited and inhibited MS specimens verified the formation of an adsorbed protective covering at the surface of MS. Tyr alone and in combination with SDS or CPC acts as mixed type inhibitor and adsorbed on the MS surface in accordance with the Langmuir adsorption isotherm. The inhibition efficiencies of Tyr or Tyr mixed with SDS or CPC obtained by weight loss, EIS and potentiodynamic polarization measurements are in good agreement and find support from theoretical quantum chemical parameters.